Strategies for Improving Higher Order Thinking Skills in Teaching and Learning of Design and Technology Education - Chinedu, Caleb Chidozie; Olabiyi, Oladiran Stephen; Kamin, Yusri Bin (Journal of Technical Education and Training, 2015)
Higher order thinking skills (HOTS) should be an integral part of teaching and learning especially at the higher education level. Thinking skills lessons should be part of the curriculum if students are to solve problems individually, cooperatively and creatively. Teachers on the other hand must be conversant with relevant techniques needed for teaching higher order thinking. An in-depth review of literature reveals that teachers are faced with the problem of how to prepare and teach higher order thinking skills in design and technology education. This paper is a library based work; and data were collected from textbooks, journal articles and internet search. The paper critically examined existing practices in the teaching of higher order thinking skills in design and technology education. Some of the key features mentioned were the use of concept, inferences, visualization, and schemas, among others. Recommendations for practice change were made regarding the development of HOTS.